Interfirm Networks: Franchising, Cooperatives and Strategic Alliances - Windsperger, J (Springer, 2015)
The organization of interfirm networks, such as alliances, cooperatives, franchise and retail chains, has become an important research topic in the field of economics, marketing, strategic management, and organization theory. This book contributes to the literature on formal and informal inter-organizational governance by providing new insights on contract design, ownership, evolution of cooperation, role of social capital and performance in franchising networks; includes topics of loyalty, reputation and organizational form as well as performance of cooperatives, and discusses the relationship between formal and relational governance in alliances, governance structures of innovation activities, dynamics of interfirm conflicts, and network externalities and alliance formation.